Differentials in Female Age at Marriage in Pakistan: Have they Changed or Not? - Aneel Shahzad (NUST Journal of Social Sciences and Humanities, 2021)
Age at marriage is an important factor to study the marriage patterns of a country because of strong relationship between age at first marriage and childbearing. In this study, effects of one major socio-cultural factor female education and place of residence have been illustrated. The present study attempted to find differentials in female age at marriage in Pakistan since Pakistan has begun to face early demographic transition since 90’s. The investigation of differentials in female age at marriage in this study is generally based on data analysis of Pakistan Demographic and Health Survey (PDHS) 2006-07. While comparative analysis also discussed in a separate section with findings of PDHS, 2012-13. The age at first marriage of women lived in major urban areas seemed to carry with them the influence of the urban lifestyle and are also influenced by the educational enrollment opportunities.